Diseño de una máquina de soplado de termoplásticos. - Aymara Montaguano, Jonathan Javier (2020)
This project aims to design an HDPE blowing machine the subject aimed to generate a source of validated research by software computational available to students and industries, and the possibility to tackle simulation studies by finite element method, on a topic that is becoming more important in plastics industry. The project uses qualitative methodology which considers technical specifications of the design, comparing each other the different alternatives with the criteria, the functional analysis and the most suitable solution for the design. The mechanical design of the extruder screw is carried out based on the book POLYMER EXTRUSION by Pierre G. Lafleur and Bruno Vergnes, using AUTODESK INVENTOR and AUTODESK NASTRAN software’s, thermal static studies were obtained from the most critical elements of the machine: Extruder spindle, extrusion head and also a stress study of the design structure. Is simulated blow molding process of a 100 ml container of HDPE in the simulation is made use of computational tool ANSYS POLYFLOW, where the closure of the mold and the air injection process was represented through the implementation of a viscoelastic model (parison) under isothermal conditions, with the simulation results of distribution thicknesses in container walls were obtained. CADE SIMU and FLUID SIM were used for electrical selection and pneumatic system. Work is presented as a computational solution to the main problems of blowing (burrs, insufficient melting, inadequate pressure).